Pengaruh Transparansi dan Kompetensi Aparatur Desa terhadap Efektivitas Pengelolaan Dana Desa di Desa Blubuk Kecamatan Losari Kabupaten Brebes - Heni Anggraeni; Akbar NPD Wahana; Ari Kristiana; Slamet Bambang Riono (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The effectiveness of Village Fund management is an essential indicator of good village governance in achieving accountable financial management and improving community welfare. However, its implementation continues to face various challenges, particularly regarding financial transparency and the competence of village officials. This study aims to examine the influence of transparency and the competence of village officials on the effectiveness of Village Fund management in Blubuk Village, Losari District, Brebes Regency. A quantitative approach with an explanatory research design was employed. The study involved 30 respondents, consisting of all village government officials, selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics. The findings indicate that transparency has a positive and significant effect on the effectiveness of Village Fund management. Likewise, the competence of village officials also has a positive and significant influence on the effectiveness of Village Fund management. Simultaneously, both independent variables significantly affect the effectiveness of Village Fund management, with an adjusted coefficient of determination of 88.8%, indicating that most of the variation in management effectiveness is explained by transparency and the competence of village officials. These findings imply that strengthening financial transparency and enhancing the capacity of village officials are essential strategies for improving effective, transparent, accountable, and sustainable Village Fund management.